Development of Homogeneity Requirement for Position Lights: Transformation from Subjective to Objective evaluation - Srinivas, Suhas; Veda Prabhakar, Suhas (My University, 2020)
Exterior lighting has become an important factor across all the automotive industry. Conventionally, light was only used to illuminate the road and help the users to have a clear vision of the road in the darkness but now it has become premium design feature for aesthetic appeasement. Lately users have started to identify the brand of the car by just viewing the light from the lamps. Many car-manufacturers are striving to get a homogeneous intensity of position lights. Light homogeneity has become a major factor under consideration during lamp design and development. Precedence is given to the perception of homogeneity by human eye over equipmental data of the same. This thesis aims to overcome the subjective evaluation of light homogeneity of lamps by bring in an objective approach and to generate corresponding requirement. The thesis work also aims to generate a verification method that can be integrated to the requirement generated. Using product development approach and established laws of photometry, an experimental investigation is performed inorder to determine quantifiable limits that assists the requirement. Investigation involves study on various factors that influence homogeneity such as eye perception, distance and angle of judgement, legal requirement and design intent. The thesis incorporates user study, which served as a foundation for obtaining subjective data and setting the requirement. Threshold values for intensity variation via response threshold was determined. It was investigated and verified that -13% and +9% were the threshold response variation between two regions, violation of which would deem the regions to appear inhomogeneous. The verification of requirement is methodically generated which was specific to the tools that were available.
Keywords: Homogeneity, Position Light, Requirement, Verification; Perceived Quality Illumination